2017
DOI: 10.1123/jsm.2016-0333
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sexualized and Violent Presentations of Women in Combat Sport

Abstract: This study utilizes an experimental design to investigate how different presentations (sexualized, neutral, and combat) of female athletes competing in a combat sport such as mixed martial arts, a sport defying traditional gender norms, affect consumers’ attitudes toward the advertising, event, and athlete brand. When the female athlete in the advertisement was in a sexualized presentation, male subjects reported higher attitudes toward the advertisement and the event than the female subjects. Female responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
1
9
0
1
Order By: Relevance
“…Algunos manuscritos en el pasado han identificado dos categorías de marca de atleta (en la cancha y fuera de la cancha), planteando elementos de la construcción de la marca de atleta usando estas dos dimensiones (Arai et al, 2014;Hasaan et al, 2018). Sin embargo, el mercadeo de atletas también se plantea en las publicaciones existentes (Greenwell et al, 2017;Parmentier y Fischer, 2012); por ejemplo, Yu (2005) menciona que una marca de atleta depende de dos dimensiones distintas de la vida del atleta, éxito en el campo e imagen positiva fuera del campo; mientras que Hasaan et al (2020) mencionan que las actividades de mercadeo y negocios le dan un fuerte impulso al desarrollo de la marca. En esta misma línea, Greenwell et al (2017) resaltan que el mercadeo del atleta asegura su autenticidad.…”
Section: Discussionunclassified
“…Algunos manuscritos en el pasado han identificado dos categorías de marca de atleta (en la cancha y fuera de la cancha), planteando elementos de la construcción de la marca de atleta usando estas dos dimensiones (Arai et al, 2014;Hasaan et al, 2018). Sin embargo, el mercadeo de atletas también se plantea en las publicaciones existentes (Greenwell et al, 2017;Parmentier y Fischer, 2012); por ejemplo, Yu (2005) menciona que una marca de atleta depende de dos dimensiones distintas de la vida del atleta, éxito en el campo e imagen positiva fuera del campo; mientras que Hasaan et al (2020) mencionan que las actividades de mercadeo y negocios le dan un fuerte impulso al desarrollo de la marca. En esta misma línea, Greenwell et al (2017) resaltan que el mercadeo del atleta asegura su autenticidad.…”
Section: Discussionunclassified
“…Past studies have identified two categories of athlete brand (on-field and off-field) and have discussed brand construction of athletes using these two dimensions (Arai et al, 2014;Hasaan et al, 2018). However, the marketing of an athlete is also discussed in the literature (Greenwell et al, 2017;Parmentier & Fischer, 2012). For instance, Yu (2005) mentioned that an athlete brand is dependent upon two different dimensions of an athlete's life -on-field success and off-field positive image -while Hasaan, Javani, Fisne, & Sato (2020) mentioned that business and marketing activities boost athlete branding.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Yu (2005) mentioned that an athlete brand is dependent upon two different dimensions of an athlete's life -on-field success and off-field positive image -while Hasaan, Javani, Fisne, & Sato (2020) mentioned that business and marketing activities boost athlete branding. In this vein, Greenwell et al (2017) noted that athlete marketing ensures the athlete's authenticity.…”
Section: Discussionmentioning
confidence: 99%
“…Though some of the articles simply used women's sport as a data source, 26 of 40 articles had a research purpose that called for research in a women's sport setting. Research with a stated purpose focusing on women's sport focused on the following topics: motives for spectating (Ferreira & Armstrong, 2004;Filo & Funk, 2005;Funk et al, 2002;Funk et al, 2003;Koo & Hardin, 2008;Lough & Kim, 2004;Kahle et al, 2001;Ridinger & Funk, 2006;Valenti et al, 2020;Zhang et al, 2003); demand/preference for women's sport (Farrell et al, 2011;Ferreira, 2009;Fink et al, 2002;Meier et al, 2016;Shackelford & Greenwell, 2005); media coverage and perceptions of women's sport (Dixon, 2002;Greenwell et al, 2017;Hallmann, 2012;Kane & Maxwell, 2011;Zhang et al, 2011); sponsorship of women's sport (Boyd & Shank, 2004;Lough & Irwin, 2001;Maxwell & Lough, 2009); psychological connection (Delia, 2020;Kerstetter & Kovich, 1997); and perceptions of LGBTQ-focused marketing (Mumcu & Lough, 2017).…”
Section: Women's Sportmentioning
confidence: 99%